2007
DOI: 10.1177/1352458507077938
|View full text |Cite
|
Sign up to set email alerts
|

Increasing incidence of multiple sclerosis among women in Lorraine, Eastern France

Abstract: This study aims to describe the prevalence and incidence rates of multiple sclerosis (MS) in Lorraine, France, and its secular trend from 1990 to 2002. Cases were sourced from the regional network of MS healthcare workers in the Lorraine region and include all cases with definite or probable MS according to Poser's criteria. We identified 2718 patients with MS on 31 December 2004. The prevalence rate was 120/100,000 (95% confidence interval [CI]: 119-121). Between 1990 and 2002, the average age- and sex-adjust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
66
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 21 publications
(31 reference statements)
2
66
2
Order By: Relevance
“…The sample comprised of 202(31.9%) male, and 431(68.1%) females. (20)(21)(22)(23)(24), While (34.1%) of the respondents Aged between (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), While (18.8%) of the respondents Aged more than 35. Table (3) that (34.4%) of the respondents belong to the eastern region, while (33.5%) of them belong to the western region, (20.4%) of them belong to the Central Region, and (7.3%) of them belong to the southern district.…”
Section: Methodology:-mentioning
confidence: 96%
“…The sample comprised of 202(31.9%) male, and 431(68.1%) females. (20)(21)(22)(23)(24), While (34.1%) of the respondents Aged between (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), While (18.8%) of the respondents Aged more than 35. Table (3) that (34.4%) of the respondents belong to the eastern region, while (33.5%) of them belong to the western region, (20.4%) of them belong to the Central Region, and (7.3%) of them belong to the southern district.…”
Section: Methodology:-mentioning
confidence: 96%
“…autoimmunity | cytokines | experimental autoimmune encephalomyelitis | gender | nuclear receptor F or reasons that remain unclear, the incidence of multiple sclerosis (MS) is increasing in women (1) and, overall, women are three times more likely to be diagnosed with MS than men (1,2). The same is true for a number of other autoimmune diseases (3).…”
mentioning
confidence: 99%
“…It has long been known that women are more likely to have MS than men, and recent reports have found a widening sex gap in diagnosis. [1][2][3] Although sex has a less dramatic effect on disease progression and clinical outcomes, several studies have reported more severe symptoms and faster progression in men. [4][5][6][7] The underlying processes thought to be involved in the development and progression of MS demonstrate significant sex differences.…”
mentioning
confidence: 99%